Scientific Mapping and Network Analysis of Scholarly Works on Short Videos in Education - Astaño, Jereme (RADINKA JAYA UTAMA PUBLISHER, 2025)
This study employs bibliometric analysis to examine research trends and emerging themes using short videos in education. Using 238 records from the Dimensions database, the investigation identifies and describes publication trends, highly cited works, leading journals, most cited authors, active countries, and country collaborations. Results indicate a consistent increase in publications, but citation trends have varied. The most cited study, Glance and colleagues, explores the pedagogical foundations of massive open online courses, while CBE-Life Sciences Education is the most cited journal. Most cited scholars include D. G. Glance, M. Forsey, M. Riley, E. A. van Vliet, N. Brouwer, and J. C. Winnips, with the United States leading in short video research and international collaborations. Co-citation analysis highlights Computers & Education as a frequently cited source and the publications from Frontiers in Psychology, Interactive Learning Environments, and Education and Information Technology. Moreover, bibliographic coupling reveals a close connection between publications on short videos and suggests strong shared intellectual content. Four themes emerge from short video publications: (1) addressing educational needs through digital learning innovations, (2) technology integration in teaching and learning in higher education, (3) short videos in post-pandemic education: opportunities and challenges, and (4) social media as a learning tool: the impact of platforms on student engagement and academic performance. Overall, this study offers valuable insights into publication trends on short videos and provides practical recommendations for future research and practice.